Improving the livelihoods of the poor and marginalized in Nepal through leasehold forestry and livestock program: A review of institutional constraints and opportunities - Regmi, BR; Albano, A; Kumar, C; Sharma, GB (Banko Janakari, 2009)
The study looks at the opportunities and constraints of the contributions made by forest institutions to improve the livelihoods of the poorest, through an analysis of the Leasehold Forestry (LF) programme in Nepal - a forestry programme that aims to help alleviate poverty of forest dependent communities by leasing degraded land to the poorest. Data and analysis were primarily based from review of literature, consultations with key informants, field visits, and complemented by the authors' direct involvement in the implementation of LF programme. Although intended to improve the lives of the poorest, the LF programme could negatively affect the poorest when it excludes them or when it causes their displacement from the land that the poorest depend for their livelihoods. Such negative impacts of LF program can be attributed to its improper implementation and design. To improve its effectiveness and impact, awareness campaigns should be improved using diverse modes of communication, more line agencies should be involved in the implementation by transferring the implementation responsibility to a district-level project coordination committee, and some programme provisions should be changed in favour of the poor. Key words: Forest institutions, leasehold forestry, poverty alleviation, Nepal doi: 10.3126/banko.v18i2.2168 Banko Janakari, Vol. 18, No. 2, 10-17